Tanaidacea (Crustacea: Peracarida) from Japan. I. Apseudomorpha from the East China Sea, Seto Inland Sea, and Nansei Islands - Larsen, Kim; Shimomura, Michitaka (Zootaxa, 2006)
The Japanese shallow water fauna of Tanaidacea is examined. One new genus in the Parapseudidae Longipedis and two new species, L. fragilis and Hoplomachus toyoshious, are described. Androgynella nipponicus is herein re-erected. Apseudes nasutus is transferred to Longiflagrum.